Analisis Risiko Produksi dan Pendapatan Usahatani Jagung di Desa Dulamayo Utara Kecamatan Telaga Biru Kabupaten Gorontalo - Novaldy I. Nadi; Amir Halid; Ramlan Mustafa (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This research was conducted in Dulamayo Utara Village, Telaga Biru District, Gorontalo Regency. This study aims to determine: 1) The risk of corn farming production in Dulamayo Utara Village, Telaga Biru District, Gorontalo Regency, 2) How much is the income of corn farming in Dulamayo Utara Village, Telaga Biru District, Gorontalo Regency. This study's population consists of corn farmers in Dulamayo Utara Village, Telaga Biru District, and Gorontalo Regency, totaling 297 people. In taking samples for this study using simple random sampling using the Solvin formula, the number of researcher samples was 39 respondents. The data analysis method used production risk analysis using the production variation coefficient formula and income analysis using the farm income formula. The results showed that using the Coefficient of Variation (CV), the corn production risk value could be calculated as 0.348 or <0.5, which can be categorized as low risk because the variation coefficient value is less than 0.5. This is also influenced by several factors, such as weather factors and pest and disease attacks, that farmers do not handle quickly and appropriately. The income obtained by 39 respondents in Dulamayo Utara Village, Telaga Biru District, Gorontalo Regency each year is Rp540,965,167. with an average/farmer of Rp13,870,902 and an average/ha of Rp9,326,897. This means that corn in Dulamayo Utara Village, Telaga Biru District, Gorontalo Regency, is quite helpful for the farmers' economy.